2007
DOI: 10.1210/en.2007-0132
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Restores Glucose Homeostasis in an Animal Model of Diet-Induced Obesity and Diabetes

Abstract: TNF-alpha plays an important role in obesity-linked insulin resistance and diabetes mellitus by activating at least two serine kinases capable of promoting negative regulation of key elements of the insulin signaling pathway. Pharmacological inhibition of TNF-alpha is currently in use for the treatment of rheumatoid and psoriatic arthritis, and some case reports have shown clinical improvement of diabetes in patients treated with the TNF-alpha blocking monoclonal antibody infliximab. The objective of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 37 publications
11
83
0
6
Order By: Relevance
“…In addition, infliximab, one of these commercial anti-TNF biological agents, was tested in obese diabetic mice, and it improved insulin signal transduction in muscle, liver, and hypothalamus. In doing so, it completely restored the activity of insulin-induced insulin receptor, insulin receptor substrate-1, and receptor substrate-2 tyrosine phosphorylation and Akt and forkhead box protein O1 serine phosphorylation (Araú jo et al, 2007). In the same vein, others have reported that insulin signaling in endothelial progenitor cells, measured by the phosphorylated to total Akt ratio, was reduced by 56% on exposure to TNF (Desouza et al, 2011).…”
Section: Tumor Necrosis Factor and Insulin Resistancementioning
confidence: 81%
“…In addition, infliximab, one of these commercial anti-TNF biological agents, was tested in obese diabetic mice, and it improved insulin signal transduction in muscle, liver, and hypothalamus. In doing so, it completely restored the activity of insulin-induced insulin receptor, insulin receptor substrate-1, and receptor substrate-2 tyrosine phosphorylation and Akt and forkhead box protein O1 serine phosphorylation (Araú jo et al, 2007). In the same vein, others have reported that insulin signaling in endothelial progenitor cells, measured by the phosphorylated to total Akt ratio, was reduced by 56% on exposure to TNF (Desouza et al, 2011).…”
Section: Tumor Necrosis Factor and Insulin Resistancementioning
confidence: 81%
“…The main molecular events determining this phenotype are the systemic and local production of cytokines (Howard et al, 2004;De Souza et al, 2005) and the activation of inflammatory pathways in cells of restricted areas of the hypothalamus involved in the control of feeding and thermogenesis (Howard et al, 2004;De Souza et al, 2005;Prada et al, 2005;Araú jo et al, 2007). Although it is generally accepted that consumption of fat-rich diets is among the most important environmental factors leading to obesity, little is known about the mechanisms linking dietary fats to the activation of inflammatory response and impairment of anorexigenic/thermogenic signaling in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of reports showing that endogenous (that is, in mice lacking TNF-α or TNF receptor) (22,23) or exogenous (TNF-α neutralization) interference with TNF-α signaling ameliorates insulin resistance during development of obesity (7,24), whereas other reports using similar strategies have failed to show an effect of TNF-α neutralization on insulin sensitivity (25,26). The reason for this discrepancy is unclear, but it may reflect dietary differences or differences in genetic backgrounds of the mice studied.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies in patients with chronic inflammatory conditions such as rheumatoid arthritis clearly show that quenching TNF-α activity improves insulin sensitivity, (7,8) a putative role of TNF-α in the development of insulin resistance in human obesity is unclear. There is no evidence for TNF-α release from human subcutaneous (27) and visceral adipose tissue (28) in vivo; thus challenging an endocrine link between adipose tissue and whole body insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation